2022
DOI: 10.1021/acsanm.2c03395
|View full text |Cite
|
Sign up to set email alerts
|

LaCoO3 Perovskite Nanoparticles Embedded in NiCo2O4 Nanoflowers as Electrocatalysts for Oxygen Evolution

Abstract: It is essential to design high-efficiency, stable, and inexpensive electrocatalysts for the oxygen evolution reaction (OER). We fabricate a hybrid system of perovskite LaCoO 3 with spinel NiCo 2 O 4 denoted LaCoO 3 /NiCo 2 O 4 via an in situ hydrothermal process. In situ incorporation of LaCoO 3 nanoparticles on the NiCo 2 O 4 nanoflower surface is confirmed by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) images. Benefiting from the interface engineering, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) was taken over a frequency range from 0.01 to 100 kHz at an amplitude of 5 mV, with a potential of 1.5 V vs RHE. The electrochemically accessible surface area (ECSA) was measured by obtaining cyclic voltammetry (CV) curves in the non-Faradaic region at different scan rates (20,40,60,80, and 100 mV s −1 ), while the linear slope values obtained by plotting the capacitive current density versus scan rate correspond to the electrochemical double-layer capacitance (C dl ). The ECSA was then determined by the equation: ECSA = C dl /C s , where C s was typically taken to be 0.04 mF cm −2 for nickel-based catalysts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical impedance spectroscopy (EIS) was taken over a frequency range from 0.01 to 100 kHz at an amplitude of 5 mV, with a potential of 1.5 V vs RHE. The electrochemically accessible surface area (ECSA) was measured by obtaining cyclic voltammetry (CV) curves in the non-Faradaic region at different scan rates (20,40,60,80, and 100 mV s −1 ), while the linear slope values obtained by plotting the capacitive current density versus scan rate correspond to the electrochemical double-layer capacitance (C dl ). The ECSA was then determined by the equation: ECSA = C dl /C s , where C s was typically taken to be 0.04 mF cm −2 for nickel-based catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Especially, the spinel-structured transition-metal oxide of NiCo 2 O 4 has been demonstrated to possess high theoretical catalytic activity and good electronic conductivity and is comparable to noblemetal-based electrocatalyst benchmarks. 15 nanospheres, 16 nanopolyhedrons, 15 nanowires, 17 nanorods, 18 nanosheets, 19 nanoflowers, 20 and nanoribbons 21 have been elaborately designed to boost the OER process. It is indicated that nanostructure engineering is an effective strategy to optimize the OER properties of the NiCo 2 O 4 catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the association of appropriate functional inorganic compounds is an effective approach to modulate the structural motif as well as the desired capabilities owing to the particular virtues of the inorganic compounds that are mainly incorporated into the solids structure and acting as an efficient materials energy generation and storage applications. [1,2] The exploration of low-cost and efficient bifunctional electrocatalysts for the OER, [3,4] hydrogen evolution reaction (HER), [5,6] and supercapacitors offer promising opportunities for sustainable energy sources due to the rapid depletion of fossil fuels. Promising renewable energy technolo-gies such as electrocatalytic water splitting has attracted considerable attention from researchers in recent years to find a possible solution to generate stable and sustainable clean hydrogen fuels, but the most effective state-of-the-art catalysts are noble metals such as Pt, IrO 2 , and RuO 2 in OER and HER, which are expensive and scarce, thereby extremely limiting their practical uses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cobalt-based electrocatalysts (CoP, Co 3 O 4 , CoOOH, CoSe 2 , etc.) have attracted significant attention for a variety of applications, including sensors (Hu et al, 2021b;Sari et al, 2022), supercapacitors (Rovetta et al, 2017;Li et al, 2018), lithium-ion batteries (Khan et al, 2016), and OER (Sun et al, 2021;Kubba et al, 2022). Because of their strong electrochemical activity, cobalt phosphates have attracted much attention in recent decades and have been used extensively in electrochemical energy storage and as electrocatalysts for water splitting (Shu et al, 2018;Majhi and Yadav, 2021a).…”
Section: Introductionmentioning
confidence: 99%